FAKTOR MOTIVASIONAL DAN INFORMASIONAL PENGANGGARAN PARTISIPATIF TERHADAP KINERJA SUMBER DAYA MANUSIA - Wulyasari, Windu Wulyasari (Jurnal Analisis Bisnis Ekonomi, 2004)
Participative budgeting can influence in human behavior and finally in performance. Human behavior influence by motivational effect like locus of control, motivations, perceptions and others. Many research find evidences that the motivational affect to performance in participative budgeting. Informational effect also become a focus in much research. This paper presents the influence of motivational and informational effect in participative budgeting to performance.